2009
DOI: 10.1128/aac.01594-08
|View full text |Cite
|
Sign up to set email alerts
|

Is the Recommended Dose of Efavirenz Optimal in Young West African Human Immunodeficiency Virus-Infected Children?

Abstract: We aimed in this study to describe efavirenz concentration-time courses in treatment-naïve children after once-daily administration to study the effects of age and body weight on efavirenz pharmacokinetics and to test relationships between doses, plasma concentrations, and efficacy. For this purpose, efavirenz concentrations in 48 children were measured after 2 weeks of didanosine-lamivudine-efavirenz treatment, and samples were available for 9/48 children between months 2 and 5 of treatment. Efavirenz concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 20 publications
7
43
2
Order By: Relevance
“…The effect of age on EFV CL/F in children was recently investigated using a population pharmacokinetic analysis (41). The study demonstrated a decrease in CL/F by age in patients 2.8 to 14.7 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of age on EFV CL/F in children was recently investigated using a population pharmacokinetic analysis (41). The study demonstrated a decrease in CL/F by age in patients 2.8 to 14.7 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the satisfactory pharmacokinetics of DDI, 3TC and EFV, 15,18 target DDI plasma concentrations were not always reached in some of the youngest children, probably because the pills were not enteric-coated. Dose adaptation of the three drugs for the youngest children (< 15-17 kg in weight) would probably improve efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacokinetic model was built for each drug. 15,18 For 3TC, a two-compartment model in which the slope of the distribution was assumed to be equal to the absorption rate constant adequately described the data, an allometric scaling was added.…”
Section: Pharmacokinetic Analysesmentioning
confidence: 99%
“…At the start of the trial, no EFV dosing recommendations for children less than 3 years old were available. Therefore, the EFV dosing regimen was selected through simulations based on the results of a trial conducted in Burkina Faso which recommended 25 mg/kg of body weight/day for all children 2 to 4 years of age (6).…”
mentioning
confidence: 99%